Synthesis and Cytotoxicity of Coumarin Derivatives and Nordentatin - Promsuwan, Pawantree; Yenjai, Chavi (Asian Journal of Chemistry, 2013)
Nordentatin and 10 coumarin derivatives were synthesized and evaluated for cytotoxicity. Compounds 6, 7, 9 and 13 showed cytotoxicity against the NCI-H187 cell line with IC50 value ranging of 3-7 μg/mL. Among synthesized coumarins, compounds 4 and 13 demonstrated cytotoxicity against the KB cell line with IC50 values of 3.94 and 6.44 μg/mL, respectively. Fortunately, coumarins 4 and 7 may be one of the new lead compounds for the development of anticancer agents due to reason that they showed weak and inactive against normal cells.